Consensus recommendations for the standardized histopathological evaluation and reporting after radical oesophago-gastrectomy (HERO consensus). Issue 8 (8th May 2021) - Pucher, Philip H; Allum, William H; Bateman, Adrian C; Green, Michael; Maynard, Nick; Novelli, Marco; Petty, Russell; Underwood, Timothy J; Gossage, James
SUMMARY: Background: Variation in the approach, radicality, and quality of gastroesophageal surgery impacts patient outcomes. Pathological outcomes such as lymph node yield are routinely used as surrogate markers of surgical quality, but are subject to significant variations in histopathological evaluation and reporting. A multi-society consensus group was convened to develop evidence-based recommendations for the standardized assessment of gastroesophageal cancer specimens. Methods: A consensus group comprised of surgeons, pathologists, and oncologists was convened on behalf of the Association of Upper Gastrointestinal Surgery of Great Britain & Ireland. Literature was reviewed for 17 key questions. Draft recommendations were voted upon via an anonymous Delphi process. Consensus was considered achieved where >70% of participants were in agreement. Results: Consensus was achieved on 18 statements for all 17 questions. Twelve strong recommendations regarding preparation and assessment of lymph nodes, margins, and reporting methods were made. Importantly, there was 100% agreement that the all specimens should be reported using the Royal College of Pathologists Guidelines as the minimum acceptable dataset. In addition, two weak recommendations regarding method and duration of specimen fixation were made. Four topics lacked sufficient evidence and no recommendation was made. Conclusions: These consensus recommendations provide explicit guidance for gastroesophageal cancer specimen preparation and assessment, to provide maximum benefit for patient care and standardize reporting to allow benchmarking and improvement of surgical quality.